Pengaruh Work Family Conflict terhadap Employee Performances - Livia Rahayu Ningsih; Firman Shakti Firdaus; Fajar Alamsyah, Indra (UNISBA Press, 2023)
Abstrak. Employee Performances are work results that can be achieved by employees in a company, in accordance with their respective authorities and responsibilities. One of the conditions that affect employee performances is the ability to resolve work family conflicts. This study aims to: 1) Find out how work family conflict works at PT Indoplast Footwear Indonesia. 2) Knowing how employee performances are at PT Indoplast Footwear Indonesia. 3) Knowing the magnitude of the effect of work family conflict on female employee performances in the production division of the sewing division at PT. Indoplast Footwear Indonesia. This research method is descriptive verification research with a quantitative approach. The sample in this study was obtained by probability sampling method. Data for the study population were 180 female employees and 64 female employees were obtained as the research sample.The results showed that the work family conflict of female employees in the production division of the sewing division at PT. Indoplast Footwear Indonesia has a significant effect on employee performances. The magnitude of the influence of work-family conflict on employee performance is relatively low at 25.4%. This means that the lower the work-family conflict, the higher the employee's performance. Abstract. Employee Performances merupakan hasil kerja yang dapat dicapai oleh karyawan dalam suatu perusahaan, sesuai dengan wewenang dan tanggung jawabnya masing-masing. Salah satu kondisi yang mempengaruhi employee performances adalah kemampuan untuk menyelesaikan work family conflict. Penelitian ini bertujuan untuk: 1) Mengetahui bagaimana work family conflict di PT Indoplas Footwear Indonesia. 2) Mengetahui mengetahui bagaimana employee performances di PT Indoplas Footwear Indonesia. 3) Mengetahui besarnya pengaruh work family conflict terhadap employee performances wanita Bagian produksi divisi sewing di PT. Indoplas Footwear Indonesia. Metode penelitian ini adalah penelitian deskriptif verifikantif dengan pendekatan kuantitatif. Sampel dalam penelitian ini diperoleh dengan metode probability sampling. Data populasi penelitian sebanyak 180 karyawan wanita dan diperoleh 64 karyawan wanita sebagai sampel penelitian.Hasil penelitian menunjukan bahwa work family conflict karyawan wanita Bagian produksi divisi sewing di PT. Indoplas Footwear Indonesia berpengaruh signifikan terhadap employee performances. Besarnya pengaruh Work-family conflict terhadap kinerja karyawan relatif rendah yakni sebesar 25,4% Artinya semakin rendah work family conflict maka akan meningkatkan kinerja karyawan.